Commentary on the United Nations Convention on the Rights of the Child, Volume 38 Article 38 : Children in Armed Conflicts. - Ang, Fiona (BRILL, 2005)
This volume constitutes a commentary on Article 38 of the United Nations Convention on the Rights of the Child. It is part of the series, A Commentary on the United Nations Convention on the Rights of the Child, which provides an article by article analysis of all substantive, organizational and procedural provisions of the CRC and its two Optional Protocols. For every article, a comparison with related human rights provisions is made, followed by an in-depth exploration of the nature and scope of State obligations deriving from that article. The series constitutes an essential tool for actor.